Research on Optimisation Methods of Intelligent Building Energy Management System - Mai, Hailin (Transactions on Engineering and Technology Research, 2024)
In recent years, the development of smart building management has gained significant momentum, driven by the increasing need for sustainable development and efficient resource utilization. This demand has led to advancements in technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and Supervisory Control and Data Acquisition (SCADA) systems. This paper explores the optimisation methods for Intelligent Building Energy Management System (IBEMS) with a focus on the integration of IoT, AI, and SCADA systems. The study begins by defining IBEMS and its components, highlighting the role of advanced technologies in achieving efficient energy management, improved operational performance, and enhanced occupant comfort. The paper analyses real-time monitoring and automation capabilities and examines how SCADA systems contribute to energy optimization and fault detection. Additionally, the application of multi-criteria decision-making (MCDM) models and activity-based costing (ABC) methods is discussed as a means to enhance the decision-making process and cost management in intelligent buildings. The significance of this study is to explore the optimization of IBEMS to improve energy efficiency, reduce carbon emissions and promote sustainable development. At the same time, it provides real-time energy management solutions that support global environmental goals and advance smart building technologies.